Employing field trip approach to promote active learning / Anis Hasliza Abu Hashim-De Vries and Kamisah Ariffin - Abu Hashim-De Vries, Anis Hasliza; Ariffin, Kamisah (2008)
There are a lot of approaches that a lecturer can employ to enhance students' learning. A well-planned field trip can bring excitement and promote active learning among the students. Field trips are able to provide unique hands-on opportunities for learning experience that cannot be offered within the classroom. This paper discusses the advantages of employing the field trip approach in the teaching and learning process. Based on a real learning experience, the writers believe that field trips that are designed around the specific course and educational objectives can benefit the students as they are able to make connection between the field trips and the concepts that they learn in the course. Being involved in a field trip can encourage the students to apply the knowledge obtained from a real life experience into the related course.